A Novel Germline Compound Heterozygous Mutation of BRCA2 Gene Associated With Familial Peripheral Neuroblastic Tumors in Two Siblings - Yeran Yang; Yeran Yang; Yeran Yang; Jiwei Chen; Hong Qin; Yaqiong Jin; Yaqiong Jin; Yaqiong Jin; Li Zhang; Shen Yang; Huanmin Wang; Libing Fu; et al. (Frontiers in Genetics, 2021)
ObjectivesTo investigate the genetic variants that are responsible for peripheral neuroblastic tumors (PNTs) oncogenesis in one family case.Materials and MethodsOne family was recruited, including the healthy parents, sister affected by neuroblastoma (NB), and brother who suffered from ganglioneuroma (GN). Whole-genome sequencing (WGS) of germline DNA from all the family members and RNA-seq of tumor RNA from the siblings were performed. Mutants were validated by Sanger sequencing and co-IP was performed to assess the impact of the mutant on chemosensitivity in the SH-SY5Y cell line.ResultsA novel compound heterozygous mutation of BRCA2 was locked as the cause of carcinogenesis. One allele was BRCA2-S871X (stop-gain) from the siblings’ mother, the other was BRCA2-N372H (missense) from their father. This novel compound heterozygous mutations of the BRCA2 gene associated with PNTs by disordering DNA damage and response (DDR) signal pathway. Moreover, chemosensitivity was reduced in the NB cell line due to the BRCA2-N372H mutant.ConclusionIn summary, these results revealed a novel germline compound heterozygous mutation of the BRCA2 gene associated with familial PNTs.